Ladin and its speakers: Multilingual repertoires and language attitudes - Fiorentini, Ilaria (Revue transatlantique d'études suisses, 2025)
This paper explores the sociolinguistic situation of Dolomitic Ladin, a Rhaeto-Romance minority language spoken in various varieties in northeastern Italy, in the regions of Trentino-South Tyrol and Veneto. The area has historically been multilingual, and since the beginning of the 20th century, there have been no monolingual adult Ladin speakers. The main objective of this paper is to describe the current state of multilingualism in the different areas of the Ladin-speaking region, identifying speakers’ language repertoires, the domains in which the different languages are used, and the attitudes that speakers exhibit toward them. The analysis will be based on both quantitative and qualitative data collected through surveys (e.g., Survey Ladins, CLaM 2021) and interviews.